Kurdistan region: A country profile - Kirmanj, Sherko (Universiti Utara Malaysia Press, 2013)
At the end of the Second Gulf War in early 1991, the Kurdish people in Iraq rose against Saddam Hussein’s regime by liberating most of the areas inhabited by them.However, within a few weeks, the uprising was crushed.The Iraqi army’s attack on Kurdish cities and villages and its retaliation against the Kurdish forces and civilians led to a mass exodus of the Kurds to Iran and Turkey.The international community’s intervention resulted in the creation of the northern no-fly-zone by the UN Security Council.This facilitated the return of most of Kurdish refugees back to their habitat.But the continued pressure by the Kurds on the regime forced the government to withdraw its forces, as well as the administrative units from parts of Kurdistan in October 1991.The Kurds then filled the vacuum created by holding elections in 1992, and thus began self-governance in the region.The areas under the control of Kurdish authorities since then came to be known as the Kurdistan Region (RG) which was a self-declared federal region in Iraq until 2005 when the Iraqi constitution officially recognized the region of Kurdistan, along with its existing authorities, as a federal region in Iraq. The KR is located in north and north eastern parts of Iraq, Syria is to the west, Iran to the east, and Turkey to the north. Its area is 40,643 square kilometers with population of 5,351,276 (estimated).The city of Erbil is the capital of the Region.Kurdish and Arabic are the official languages in the Region. However, Turkmeni, Assyrian and Armenian are also used by the respective communities in some areas. In addition to Kurds a diverse collection of ethnic and religious groups live side-by-side in the Region — including Arabs, Turkmen, Chaldeans, Syriacs, Assyrians, Yazidis, Kakayi and Shabaks.The region is geographically diverse, from hot plains to cooler mountainous areas where snow falls in the winter.